The role of religious coping on the psychological distress of women with breast cancer - Supatmi, Supatmi; Nadhiroh, A'im Matun; Reliani, Reliani; Muzamil, Akhmad; Ab Latif, Rusnani (Pediomaternal Nursing Journal, 2025)
Introduction: Breast cancer poses a psychological burden on the patient due to the disease itself or the treatment that must be undergone. The existence of religious coping for women with breast cancer will make them continue to think positively about their situation. Methods: This study used a descriptive research design based on a quantitative approach with the aim of analyzing religious coping on psychological distress in breast cancer patients. A sample of 88 breast cancer patients was carried out by non-probability convenience sampling with. The instrument in this study uses the RICOP Brief, while the psychological distress instrument is the Kessler Psychological Distress Scale (K10) The collected data were analyzed using the Spearman rho analysis test with a confidence interval of 95% with α = .05. Results: It was obtained that the effect of positive religious coping on psychological distress was P-value = .034 ≤ .05 with r = -.312 for positive religious coping on psychological distress with a P-value = .992 with r = -.001. The higher the use of positive religious coping strategies, the lower the level of psychological distress. Conclusion: Positive religious coping has a significant effect on psychological distress in women with breast cancer with negative values, where high positive religious coping will reduce the psychological distress that occurs, The use of religious coping has no effect on psychological distress in women with breast cancer. Keywords: breast cancer; psychological distress; religious coping